Effect of monsoon depression of east coast at some distant region in west - LAL , ASOI; SUNDAR, R. S. (MAUSAM, 1998)
Whenever a vortex or system of low or depression forms over head bay during Monsoon months, the west coast experiences heavy rainfall. These heavy rainfall occurrences are usually higher than the normal rainfall. An attempt has been made in this study to visualise the easterly wave model during monsoon months with the help of satellite imageries. The rain is expected heavy and wide spread over Madhya Maharashtra and South Gujarat when third sector of the wave covers these areas, as visualised in satellite wave and depression or vortex lies in the 5th or 6th sector of the wave.